2017
DOI: 10.1002/maco.201609276
|View full text |Cite
|
Sign up to set email alerts
|

High temperature corrosion and electrochemical behavior of HVOF sprayed Inconel 718 coating using an innovative device: HTCMD

Abstract: Inconel 718 is one of the most commonly used nickel‐based superalloy materials in petroleum industry due to its high temperature mechanical properties and corrosion resistance. Generally, corrosion resistance assessment of materials at high temperature condition is a challenging task and most of the previous studies in this area were based on estimation of weight‐loss in the sample, which cannot provide accurate results, and it could be very time‐consuming. In this study, a high temperature corrosion measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The excellent corrosion resistance of Inconel 718 could be attributed to the formation of Cr 2 O 3 thin layer on the surface, but the passive layer was not stable and will be destroyed with the time increased in chloride ions solution. In Figure , the FeCl 3 immersion test shows that during the same immersion time, HT950 treated sample showing much weak corrosion attack on the surface, which indicated that HT950 treated sample have lower corrosion rate.…”
Section: Resultsmentioning
confidence: 99%
“…The excellent corrosion resistance of Inconel 718 could be attributed to the formation of Cr 2 O 3 thin layer on the surface, but the passive layer was not stable and will be destroyed with the time increased in chloride ions solution. In Figure , the FeCl 3 immersion test shows that during the same immersion time, HT950 treated sample showing much weak corrosion attack on the surface, which indicated that HT950 treated sample have lower corrosion rate.…”
Section: Resultsmentioning
confidence: 99%